The scope and severity of white‐nose syndrome on hibernating bats in North America. Issue 5 (20th April 2021) - Cheng, Tina L.; Reichard, Jonathan D.; Coleman, Jeremy T. H.; Weller, Theodore J.; Thogmartin, Wayne E.; Reichert, Brian E.; Bennett, Alyssa B.; Broders, Hugh G.; Campbell, Joshua; Etchison, Katherine; Feller, Daniel J.; Geboy, Richard; et al.
Abstract: Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis, Myotis lucifugus, and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning. Abstract : Article impact statement : Data sharing and coordinated monitoring are needed to assess species' response to threats to inform conservation planning at relevant scales. Abstract : Alcance y Severidad del Síndrome de Nariz Blanca en los Murciélagos Hibernando en América del Norte Resumen: La evaluación del alcance y la severidad de las amenazas es necesaria para los análisis de impacto sobre las poblaciones que se usan para orientar a la planeación de la conservación. La evaluación cuantitativa de amenazas con frecuencia requiere de programas de monitoreo que proporcionen datos confiables en escalas espaciales y temporales, aunque dichos programas pueden ser difíciles de justificar hasta que exista un estresante aparente. Gracias a una movilización de esfuerzos de las agencias de manejo de fauna para registrar los conteos invernales de murciélagos hibernadores, recopilamos datos para cinco especies en más de 200 sitios a lo largos de 27 estados de EUA y dos provincias canadienses entre 1995 y 2018 para determinar el impacto del síndrome de nariz blanca (SNB), una enfermedad mortal de los murciélagos hibernadores. Estimamos declinaciones en los conteos invernales de las colonias de murciélagos en sitios en donde el hongo invasivo que ocasiona el SNB ( Pseudogymnoascus destructans) había sido detectado para evaluar el impacto de amenaza del SNB. Tres especies que se encuentran bajo valoración por parte del Servicio de Pesca y Vida Silvestre de los EUA ( Myotis septentrionalis, Myotis lucifugus y Perimyotis subflavus ) tuvieron una declinación de más del 90%, lo que justifica la clasificación de la severidad de la amenaza del SNB como extrema con base en el criterio usado por NatureServe. El alcance de la amenaza del SNB definido por el criterio de NatureServe fue desde amplio (36% de la distribución de Myotis lucifugus ) hasta dominante (79% de la distribución de Myotis septentrionalis ) para estas especies. Las declinaciones de otras dos especies ( Myotis sodalis y Eptesicus fuscus ) fueron menos severas, pero de igual manera quedaron clasificadas desde moderada hasta seria con base en los criterios de NatureServe. El intercambio de datos entre las jurisdicciones proporcionó una evaluación completa del alcance y la severidad de la amenaza del SNB e indicó las diferencias regionales que pueden guiar a los esfuerzos de respuesta realizados en las jurisdicciones internacionales, nacionales, estatales o provinciales. Evaluamos el impacto de amenaza de una enfermedad infecciosa emergente mediante la combinación de los esfuerzos de monitoreo que sobrepasan fronteras jurisdiccionales y demostramos la importancia que tienen para la planeación y la evaluación basadas en datos de la conservación los programas de monitoreo coordinados, como el Programa de Monitoreo de los Murciélagos Norteamericanos (NABat).